PENINGKATAN KAPASITAS GURU PAUD DALAM IMPLEMENTASI TRANSISI PAUD KE SD YANG MENYENANGKAN DI WILAYAH REGIONAL KETAPANG - Baharuddin, Baharuddin; Santosa, Hardi; Amirullah, Gufron; Saputra, Dendy Wijaya (LPPM Universitas Islam 45 Bekasi, 2025)
The transition from Early Childhood Education (PAUD) to Elementary School (SD) often causes problems such as children's social-emotional and academic unpreparedness. This is due to the difference in learning approaches between PAUD, which is play-based, and SD, which is more formal. The purpose of this community service is to improve PAUD and SD teachers' understanding of holistic transition principles centered on children's needs. Training teachers in designing play-based and project-based transition activities. The activities were conducted over two days at the Grand Zuhri Hotel in Ketapang District, involving 50 participants comprising teachers and school principals. The methods used included: workshops, simulations and practical exercises, group discussions, and evaluations through pre-tests, post-tests, observation of participation, and participant satisfaction questionnaires. The results of the program showed that participants were able to design play-based activities such as exploring the elementary school environment and role-playing, as well as mastering simple assessment tools to monitor children's social-emotional development. This program had a significant impact on enhancing teachers' capacity to create enjoyable PAUD-SD transitions, reducing transition shock in children through a play-based approach. The collaboration formed between teachers, parents, and educational institutions strengthened systemic support for children's readiness. The activity outcomes also serve as policy recommendations for the Education Department to integrate transition modules into ongoing teacher training, while also serving as a best practice model that can be adapted in other regions of Indonesia.